To smoke a wasp's nest - Browne, Margaret F., author; Beachy-Quick, Dan, advisor; Steensen, Sasha, committee member; Emami, Sanam, committee member (Colorado State University. Libraries, 2020)
This manuscript centers on destroying wasps' nests as a central metaphor for a kind of exorcism of a deep-seated grief. Grief for a time and place in a family's history, for the traumas they experienced that left long-lasting wounds, and for the loss of a matriarch—who loomed so large as what felt archetypally "mother". In many ways, this is an elegy for a mother who can never be—a permanent, vast mother able to carry and hold us and all of the grief of being a person in the world, as we were once held as children. It's an elegy for the knowledge that there is no such mother, and inevitably, we cannot return to that place of childlike innocence and comfort.